Application of Moodle-Based Learning for English Students - Novia, Lely; Noni, Nurdin; Samtidar, Samtidar (Universitas Negeri Makassar, 2024)
Abstract. The rapid growth of digital technology has considerably impacted the education industry, prompting the transformation of traditional teaching methods to suit the demands of the twenty-first century. This study investigates Moodle-based learning for English students, motivated by the desire to improve engagement, accessibility, and learning results through novel educational technology. The premise for this study stems from Moodle's potential to alter the learning experience by delivering dynamic, adaptable, and student-centered educational settings. This study aims to assess Moodle's usefulness in enhancing English language competency, identify student problems, and provide recommendations for maximizing its use. The research methodology is descriptive quantitative research using a questionnaire. There are 306 respondents to this research. The findings show that Moodle-based learning has been highly welcomed by students, improving their knowledge of English ideas, delivering high-quality learning materials, and allowing for convenient access and interaction with instructors and peers. Students reported better learning outcomes, increased independence, and more effective time management. However, issues such as digital literacy and access to technology were discovered.Keyword: Moodle-based learning, implementation, online learning